Aspirations of Retailers and Visitors Towards the Regeneration of Declining Streets in Cities. Issue 1 (15th June 2018) - Turner, Philip; Bahaj, AbuBakr; Teli, Despoina
City Centre retail spaces are integral to the sustainability of cities, and within this hierarchy secondary shopping streets, which act as hubs for local communities and businesses, have become isolated. There is now a recognised need for academic studies to reverse these trends in these areas, especially in a UK context. This work analysed and compared stakeholders' perceptions of urban interventions in a declining secondary retail area in Southampton. The investigation was based on interviews and surveys of stakeholders, as well as observational studies enhanced through analysis of secondary data. This paper presents the outcomes of such investigations addressing the perceptions and behaviours of retailers and visitors, focusing on where these are aligned or divided. The overall results reveal that retailers are more concerned with 'static' improvements, such as parking provisions or building façade improvements, while visitors are concerned with active and spatial improvements, with street level interventions being the most important. The results also show that (a) whilst retailers may believe that they understand what visitors require; they differ greatly and (b) many aspirations of retailers are costly or dependant on other businesses' intentions. Visitor's desires: include the reuse of vacant stores and creation of public space, which are far more viable, and can be enacted by governance. Such options should be trialled as a means to educate and improve understanding of less traditional interventions. The paper also provides input on ways to make these failing areas more sustainable through a shared vision and wide applicability.